Smart Dust Bin With Automatic Lid and Buzzer Alarm - Aida Mahdalena Lubis; Fabio Sarmento Freitas Guterres; Joana Victorine Harryanto; Mia Galina (Journal of Electrical And Electronics Engineering, 2020)
Touching dustbins by hand often are problematic by some people due to questionable hygiene conditions. This, along with laziness to dispose garbage properly may also be a factor that makes people hesitate to dispose of garbage. This project aims to make use of microcontroller technology to create a Smart Dust Bin. This prototype would have a lid that automatically open when a hand is approaching it which eliminates the need to physically touch the bin. The device also has internal alarm system which will sound whenever the content reaches level high enough inside the bin. Upon a test, these two features work properly.